2004
DOI: 10.1093/molehr/gah024
|View full text |Cite
|
Sign up to set email alerts
|

The size of a microsatellite polymorphism of the haem oxygenase 1 gene is associated with idiopathic recurrent miscarriage

Abstract: Endothelial damage, impaired microvascularization and immune maladaptation have been described as aetiological factors in recurrent miscarriages. We investigated the relationship between idiopathic recurrent miscarriage (IRM) and a (GT)(n) repeat microsatellite polymorphism of the gene encoding haem oxygenase 1 (HO-1), known to modulate immune functions such as T-helper (TH) cell function and to be associated with cardiovascular disease. We investigated 162 women with IRM and 129 healthy, post-menopausal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 27 publications
1
57
0
Order By: Relevance
“…It remains to be elucidated whether the low HOs levels are a consequence of the fetal tissue damage or the cause of abortion (i.e., due to a different genetic background in the F 1 tissue). Accordingly, Denschlag et al (36) observed that a microsatellite polymorphism of the HO-1 gene (leading to low levels of HO-1 expression) is associated with ). Statistical analysis was done by using the nonparametric Kruskall-Wallis test followed by Mann-Whitney U test.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be elucidated whether the low HOs levels are a consequence of the fetal tissue damage or the cause of abortion (i.e., due to a different genetic background in the F 1 tissue). Accordingly, Denschlag et al (36) observed that a microsatellite polymorphism of the HO-1 gene (leading to low levels of HO-1 expression) is associated with ). Statistical analysis was done by using the nonparametric Kruskall-Wallis test followed by Mann-Whitney U test.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 mRNA expression was quantified by real-time PCR (Light Cycler Instrument; Roche Diagnostics, Basel, Switzerland) utilizing glyceraldehyde-3-phosphate dehydrogenase (GAPD) as an internal standard. Primers were synthesized according to the published sequences (35). Standard curves were prepared for the target and reference genes by amplification of diluted plasmid DNA containing the target sequences (pGem+ vector; Promega Corp., Madison, USA).…”
Section: Assessment Of Ho-1 Mrna Expressionmentioning
confidence: 99%
“…Length of these repeats is associated with variability in basal HO-1 gene expression levels and disease states (12,14). One example of a human HO-1 deficiency has been reported from Japan (15).…”
Section: Scientific Investigationsmentioning
confidence: 99%